A Review of the Food and Drug Administration Adverse Event Reporting System for Tramadol-Related Hypoglycemia. Issue 3 (March 2020) - Juba, Katherine M.; van Manen, Robbert P.; Fellows, Shawn E.
Background: Hypoglycemia is a rare adverse effect of tramadol that is described in the medical literature and package insert.Objective: The purpose of this study was to review reports of tramadol and hypoglycemia in the Food and Drug Administration Adverse Event Reporting System (FAERS) database to determine a potential association.Methods: Disproportionality analysis with Bayesian correction was used to compare tramadol and hypoglycemia with other medications in FAERS. The results were considered significant if the fifth percentile of the Empirical Bayesian geometric mean distribution (EB05) >2. Logistic regression odds ratios was used to determine if age, diabetes medications, and renal insufficiency masked the disproportionality of hypoglycemia, with the fifth percentile of the logistic regression odds ratio (LR05) >2 indicating a potential signal. The Interaction Signal Score (INTSS) was computed to determine the influence of predisposing risk factors on the signal.Results: A total of 605 cases of tramadol-associated hypoglycemia were reported, but our results were not significant (EB05: 1.590). Tramadol-associated hypoglycemia was significant in patients who did not take diabetes medications (EB05: 2.256; LR05: 2.2104). Renal insufficiency was not found to increase the risk of tramadol-associated hypoglycemia (INTSS: 0.865). There was a significant signal for tramadol-associated hypoglycemia in patients aged 0 to 1 year (LR05: 3.0240) and 2 to 4 years (LR05: 2.6853).Conclusion and Relevance: Results of our analysis suggest a potential signal between hypoglycemia and tramadol use in patients not taking diabetes medications. Our results do not support a predisposition for tramadol-associated hypoglycemia in patients with renal insufficiency, increasing age, and/or diabetes as noted in the tramadol package insert.